Grand Desain, Inisiasi Wisata Halal dan Edukasi Pasar Ternak Kedung Berkah Dalam Peningkatan Pendapatan Bumdes Desa Tirta Kencana Kecamatan Rimbo Bujang Kabupaten Tebo - Ridhwan, Ridhwan; Amir, Amri; Rafiqi, Rafiqi; Alissa, Evalina; Amri, Ary Dean; Inggriani Powa, Natasya (PT. Alahyan Publisher Sukabumi, 2025)
This community service program aims to improve the economic well-being of the residents of Tirta Kencana Village through the development of halal tourism and livestock market education. The strategies implemented include the construction of Muslim-friendly tourism infrastructure, community training on halal tourism standards, and education for livestock farmers to enhance livestock productivity and market access. Through the